Food Estate Policy in Humbang Hasundutan Regency, North Sumatra Province, from the Perspective of Maslahah Mursalah - Caniago, Addri; Nurasiah, Nurasiah (Journal of Law, Politic and Humanities, 2024)
Maslahah mursalah refers to an entity or thing that is rationally beneficial, given its potential to benefit mankind or prevent its damage. The implementation of the Food Estate policy in Humbang Hasundutan Regency, North Sumatra Province is one example. The main objective of this analysis effort is to analyze the implementation of the Food Estate policy in the Humbang Hasundutan District. Farmers provided primary data, and secondary data were extracted from supporting literature for this study. Data collection methods included interviews and documentation. The results of this study can be concluded that the food estate policy is considered unsuccessful due to the lack of training and socialization assistance provided by the government to farmers, the initially hard land must be plowed so that it becomes peatland and takes a long time, the extreme weather in Humbahas which is erratic, the lack of knowledge of farmers in managing food estate, and the lack of supporting facilities for farmers in managing land.